Asthma as a link between chest illness in childhood and chronic cough and phlegm in young adults. Issue 6626 (26th March 1988) - Strachan, D P; Anderson, H R; Bland, J M; Peckham, C
Abstract : The link between chest illnesses in childhood to age 7 and the prevalence of cough and phlegm in the winter reported at age 23 was investigated in a cohort of 10 557 British children born in one week in 1958 (national child development study). Both pneumonia and asthma or wheezy bronchitis to age 7 were associated with a significant excess in the prevalence of chronic cough and phlegm at age 23 after controlling for current smoking. This excess was largely attributable to the association of cough and phlegm at age 23 with a history of asthma or wheezy bronchitis from age 16. When adjustment was made for recent wheezing, current cigarette consumption, previous smoking habit, and passive exposure to smoke the relative odds of cough or phlegm, or both, in subjects with a history of childhood chest illness was 1·11 (95% confidence interval 0·97 to 1·27). When analysed separately asthma, wheezy bronchitis, and pneumonia up to age 7 did not significantly increase the prevalence of either cough or phlegm. The explanation for the observed continuity between chest illness in childhood and respiratory symptoms in later life may lie more in the time course of functional disturbances related to asthma than in the persistence of structural lung damage.